Perception of lecturers on the core curriculum minimum academic standard (CCMAS) at Tai Solarin Federal University of Education - Emmanuel Sunday Osiyemi; Simon Iruoghene Imoh; Kayode John Olusanya; Olalekan Rahman Adebayo; Rachael O. Agbajaeola (International Journal on Education Insight, 2026)
The implementation of the Core Curriculum Academic Standards (CCMAS) has attracted the attention of lecturers on whether a 30% flexibility can be really practicable within universities. The study examined the perception of lecturers on Core Curriculum Minimum Academic Standard at Tai Solarin Federal University of Education. The descriptive survey research design was used. The study population comprised all lecturers at Tai Solarin Federal University of Education with a sample of 61 lecturers. Data were collected with the use of researchers developed questionnaire tagged “Lecturers Perception of CCMAS Questionnaire (LP-CQ) with a reliability coefficient of .75. The results indicated that the level of lecturers’ awareness and understanding was high (=3.12), perceptions of academic autonomy and curriculum flexibility was moderate (=2.78), perceived benefits of implementing CCMAS was moderate (=2.80), and perceived challenges of implementing CCMAS was moderate (=2.89). The study concluded that the effective implementation of CCMAS is not the sole issue related to the policy design, but also to sustain professional growth, sufficient institutional commitment, and real flexibility of the curriculum that enables the universities to innovate within their unique environments. It was recommended, among others, that NUC should increase institutional contribution beyond 30 percent whereas universities must make use of its contribution to the maximum to demonstrate local realities, industry demands and new global tendencies.